Towards a Learner-Centred Approach to Design Role-Play Instruments for ILP Studies: A Study Based On Complaints - Beltrán-Palanques, Vicent (Complutense Journal of English Studies, 2020)
Role-play tasks have been widely used in pragmatic research to explore spoken interaction. This instrument consists of situational scenarios purposefully designed to make participants elicit specific pragmatic data in controlled situations (Kasper & Youn 2017, Félix-Brasdefer 2018). Notwithstanding the widespread use of role-plays, some drawbacks have been identified concerning design (Hudson et al. 1995, Trosborg 1995, Youn 2015) and real-life consequences (Al-Gahtani & Roever 2012). Against this backdrop, this study presents a learner-centred approach to design situational scenarios based on participants’ examples of complaint situations. Specifically, an exemplar generation task and a likelihood questionnaire (Jianda 2006a, 2006b) were used to elaborate the role-play task. The study reports on the implementation of the learner-centred approach and its effectiveness to construct a role-play task. Furthermore, using retrospective verbal reports, this study discusses whether participants’ engagement in the design of the role-play task encouraged them to act out the situations, as they would do it in real-life contexts. The study evidences the usefulness of adopting a learner-centred approach to design the role-play task. In terms of performance, it seems that, in general, the participants would exhibit similar pragmatic behaviour in a real context. However, they were aware of the lack of real consequences role-play tasks carry.